PURCHASING DECISIONS REVIEWED FROM PRODUCT VARIANTS, STORE ATSMOSPHERE AND LIFESTYLE (Case Study at Excelso Caffe, The Park Mall Solo Baru) - Muhammad Sholihiin; Sudarwati Sudarwati; Sarsono Sarsono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Currently, businesses are required to have a strategy that can attract and maintain consumers for the sustainability of their company. The study aims to test product variants, store atsmosphere and lifestyle, against the purchase decision of Excelso Caffe at The Park Solo Baru. The research sample used Accidental Sampling techniques as many as 100 consumers, with analysis techniques using multiple linear regression methods. The results of research on product variants, store atmosphere and lifestyle together or partially had a significant effect on the purchasing decision of Excelso Caffe at The Park Solo Baru. The purchase decision can be explained by three independent variables of 37.9% and the other is influenced by other variables.